DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE SURDOPEDAGOGS THROUGH OPTIMIZATION OF INDEPENDENT EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Properly organized independent work creates the basis for students to acquire learning experience, life skills, social and professional attractiveness, opportunities for personal and self-esteem. Independent education forms professional competencies.